(untitled) (Islas, 2026)
Introduction: This article examines the most frequent online search queries related to phrasemes in an electronic dictionary of neologisms. It specifically analyzes the strategies speakers use when selecting search terms to retrieve the meanings of multiword expressions. Methods: The analysis of search terms is informed by the literature, which has identified four factors that may account for their selection: term frequency, grammatical category, position within the phraseme, and length. Results: The findings indicate that frequency is the factor with the greatest explanatory power in the selection of search terms. This result is consistent with previous studies and further confirms the central role of frequency using a dataset unprecedented in the literature. Conclusions: This analysis not only identifies the factor with the highest explanatory value, but also reveals the emergence of new strategies for retrieving phraseological information in digital environments. Frequency is confirmed as the most relevant predictor of users’ choice of search terms. Electronic dictionaries and search engines, such as Google, enable new forms of phraseological retrieval that are not constrained by the single-word structure of printed dictionaries.